TINGKAT KEPUASAN PASIEN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI TERHADAP LAYANAN ANTAR OBAT (YANTARO) DEPO FARMASI RAWAT JALAN DI RSUD H. BADARUDDIN KASIM TABALONG - Wardhani, Yoga Kusuma; Misgiati; Aditya, Mayang (Jurnal Insan Farmasi Indonesia, 2025)
The drug delivery service (YANTARO) is innovative pharmaceutical service at H. Badaruddin Kasim Regional Hospital, Tabalong, designed improve patient convenience, reduce queues, and accelerate patient access to medications. This study aims evaluate level of patient satisfaction and the factors that influence satisfaction with YANTARO service. The research employed a quantitative method with cross-sectional approach, involving 43 outpatient respondents who utilized the YANTARO service. Data were collected using a questionnaire based on the Servqual dimensions (tangibles, reliability, responsiveness, assurance, and empathy) and were analyzed descriptively. The validity and reliability tests indicated that the research instruments were valid (r-count > 0.361) and reliable (Cronbach’s Alpha 0.919 for service factors and 0.808 for patient satisfaction). The findings show  the YANTARO drug delivery service at the Outpatient Pharmacy Depot of H. Badaruddin Kasim Hospital is effective in improving patient satisfaction. The overall level patient satisfaction was high, with ease of access being the highest-rated indicator, while medication information delivery still requires improvement. The factors that most influenced patient satisfaction were the condition of  medication upon delivery and the attitude of  staff during the delivery process. Overall, the YANTARO service successfully reduced queues, saved patients’ time, and provided convenience for outpatients in obtaining their medications.